Eficacia y seguridad analgésica de la buprenorfina versus fentanyl en anestesia raquídea para pacientes sometidas a cirugía obstétrica abdominal en el hospital provincial Isidro Ayora de la ciudad de Loja durante el periodo septiembre del 2012 a marzo del 2013. - Espinosa Mora, Alex Xavier (2014)
This work had as purpose the comparison of the efficacy and safety ANALGESIC enter BUPRENORPHINE VERSUS FENTANYL, as well as determine the most common adverse effects. The study was conducted at the Provincial Isidro Ayora Hospital of the city of Loja in the period from September 2012 to March 2013, with a universe of 100 patients, which attended the OBSTETRICS service requiring the realization of obstetric surgery with spinal anesthesia. The patients met the inclusion criteria and are designated them randomly in a number 50 individuals to apply 10 mg more BUPRENORPHINE 1 mcg/kg BUPIVACAINE and the 50 remaining with the conventional method of BUPIVACAINE 10 mg more FENTANYL 25 mcg intrathecal. The objectives were to assess the efficacy and postoperative analgesic duration between two opioid drugs and to determine the most frequent adverse effects. The dependent and independent variables evaluated were: time of analgesia post-surgical assessment of adverse reactions drug-induced, satisfaction of the patient, the anesthesiologist; Age, weight, handle, heart rate, systolic blood pressure, diastolic media, oxygen saturation, analgesic duration, EVA respectively. The results allowed concluding that the postoperative analgesia with BUPRENORPHINE had more effectively and safety compared with the FENTANYL, similarly failed to verify that the presence of adverse effects was greater prevalence in patients that was administered FENTANYL.